MEMBANGUN KEBHINEKATUNGGALIKAAN DENGAN SASTRA LINTAS BUDAYA - Yeni Mulyani Supriatin (Fakultas Seni Rupa dan Desain ITB, 2010)
Indonesia is a pluralist nation as well as multicultural. This dimension is realized very well by the founders of this republic that was born the motto Unity in Diversity, 'Different but the same'. Although we realize that the state Unity in Diversity, is not always easy to make it happen in the life of nation and state. History records, in the 1950s this country would not go after dealing with separatist movements seeking to secede from the republic. In contrast, during the New Order regime with near-totalitarian style of government everything occurs almost in uniformity. The governance of state errors in the New Order was then revised by presenting regional autonomy in the reform era. Regional autonomy with a chance of empowering the local culture is not without risk. The sense of narrow ethnicity could ultimately nullify the fact that our country is basically a pluralistic and multicultural nation. Therefore, on the other hand, within the framework of nation building is essential to find a kind of compromise between locality / ethnicity who grew up in the spirit of regional autonomy with the reality of Indonesia as a pluralistic and multicultural nation. A compromise between locality / ethnicity with the reality of a pluralistic state, among others can be realized with the literature across cultures / ethnicities. Almost all ethnic groups in Indonesia have folklore. Ideally, all the folklore of various regions and ethnic groups in Indonesia are summarized in a single package and incorporated into the curriculum of literature learning in primary / secondary school. Thus, from an early age students are introduced to literature / other ethnic cultures so as not to get stuck in a narrow and parochial ethnicity. Keywords: cross-cultural literature, multiculturalism, unity in diversity, nation building